TOSHKENT VOHASI MEGACHILIDAE ASALARILARI (HYMENOPTERA, APOIDEA) VA ULARNING EKOLOGIK XUSUSIYATLARI (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article discusses the ecological characteristics of bees belonging to the family Hymenoptera: Megachilidae in the Tashkent oasis, their behavior as a result of their interactions, their importance in the pollination process, and their importance in agrocenoses.